Estimation of geometric fractional Brownian motion perturbed by stochastic volatility model - Alhagyan, Mohammed; Misiran, Masnita; Omar, Zurni (Pushpa Publishing House, 2015)
This article is aimed at to derive geometric fractional Brownian motion where its volatility follow long memory stochastic volatility model, in particular the fractional Ornstein-Uhlenbech process. The innovation algorithm is utilized to simplify such derivation. A simple case of is calculated to illustrate the calculation to accompany this derivation.